(untitled) (Global Journals of Research in Engineering, 2014)
Different processes associated with complete production of fabrics are discussed briefly in this paper. An effort is made to formulate all the production steps. This paper also gives an idea of different processes and machineries used usually in a fast growing and mass productive knitdyeing factory. Major processes in all machines are discussed briefly. Different important parameters in different machines are also stated here. This paper tries to gather all the information related to knit-dyeing factory shortly. A helpful estimation of machine capacity for required production amount can be perceived from this paper. Also the existing efficiency of different processes can easily be calculated from different mathematical formulas stated here.